The Effect of Training and Work Environment on Performance of Employees Through Organizational Commitment as Intervening - Widiyastini, Reni Dwi; Handayani, Yuniorita Indah; Kusuma, Dedy Wijaya (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Work problems at the Department of Public Works, Water Resources, and Construction of Bondowoso Regency include budget constraints, technical constraints, and lack of coordination and supervision. The purpose of this study is to test and analyze the effect of training and work environment on employee performance through organizational commitment as an intervention variable on employees of the BSBK Department of Bondowoso Regency. This study is included in explanatory research with a population of 183 and a sample of 126 respondents obtained by calculating the slovin formula, the sampling technique used is purposive sampling. The data analysis technique used is Structural Equation Modeling (SEM) which is processed with Smart PLS 4.0. Based on the results of the data analysis, it shows that training has a significant effect on organizational commitment. The work environment has a significant effect on organizational commitment of the BSBK Department of Bondowoso Regency. Training, work environment and organizational commitment have a significant effect on employee performance at the BSBK Office of Bondowoso Regency. Training has a significant effect on employee performance through organizational commitment at the BSBK Office of Bondowoso Regency. The work environment has a significant effect on employee performance through organizational commitment at the BSBK Office of Bondowoso Regency. Therefore, BSBK Bondowoso Regency needs to improve training programs that are in accordance with current needs, as well as create a more ergonomic and comfortable work environment. These steps are expected to increase employee work effectiveness and support the achievement of organizational goals optimally